PENGARUH SELF EFFICACY TERHADAP KEMAMPUAN MEMECAHKAN MASALAH IPA - Fauziana Fauziana (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2022)
This research is motivated by the lack of ability to solve problems in grade 5 students. This study aims to determine the effect of self-efficacy on the ability to solve science problems. The sample in this study were 50 grade 5 students. This research is a quantitative research. Data analysis used simple linear regression. Based on the data analysis, the regression equation Ŷ = 50.333 + 0.489X is obtained. From hypothesis testing, the value of tcount is greater than ttable, namely 3. 314 > 2.010, then H0 is rejected and Ha is accepted. Thus, there is a significant effect of self-efficacy on the ability to solve science problems for grade 5 students.